Budaya Organisasi Dalam Pengembangan Kemandirian Santri Di Pesantren Ashqaf Jambi - Arpinal Arpinal; Jamrizal Jamrizal; Musli Musli (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
The purpose of this study was to understand and analyze the role of organizational culture at the Ashqaf Jambi Islamic Boarding School in developing the independence of students. Qualitative research to understand and describe the phenomenon of developing students' self-reliance at the Ashqaf Islamic Boarding School Jambi. Sources of data include in-depth interviews with students, kiai, teaching staff, and pesantren administrators, as well as participatory observations within the pesantren. The data will be analyzed thematically and using a content analysis approach to identify the main themes related to the independence of the students. The results of this work are a) Ashqaf Islamic Boarding School has proven to be a leading educational institution that provides an important role in shaping the independence of students through a holistic educational approach, strong organizational culture, and support from teachers and mentors. b) A strong organizational culture at the Ashqaf Islamic Boarding School provides a solid foundation for the development of self-sufficient students, creates a harmonious environment that supports the growth of individuals who are strong, have noble character, and are ready to face various challenges in life. c) A strong organizational culture at the Ashqaf Islamic Boarding School has a positive impact on developing the independence of students, forming empathetic characters, and preparing them to become agents of positive change in society.